Juridical Implications of Forced Marriage As A Form of Violence Against Women - Aida Dewi; Yulianus Hendrikus Billi Yulianus Hendrikus Billi (Universitas Mataram, 2026)
The practice of forced marriage in Southwest Sumba regency reflects the conflict between customary law and national law that has a serious impact on the fulfillment of human rights, especially women’s rights. One form of such practice is mating capture, which is a tradition that is still found in some Indigenous communities and is often carried out without the consent of the women who are victims. This practice causes various forms of harm, both physically, psychologically, socially, and legally, so it can be categorized as a form of violence against women. This study aims to analyze the juridical implications of forced marriage as a form of violence against women and assess the challenges of applying the law in a society that is still strong in maintaining customary values. This study uses empirical legal approach with socio-legal methods. The analysis was carried out through normative studies of national legislation, especially Law Number 12 of 2022 on Sexual Violence Crimes (TPKS law), the Criminal Code, and various international human rights instruments that have been ratified by Indonesia. The study was combined with empirical data obtained from the practice of Capture mating in the field to understand the gap between legal norms and social reality. The results showed that Article 10 of the TPKS law has expressly criminalized forced marriage and provides a stronger legal basis in protecting women. However, its implementation still faces various obstacles, including the belis culture which requires high costs, structural poverty in East Nusa Tenggara, low legal awareness of the community, and resistance from some Indigenous communities to state intervention. Although law enforcement officials began to implement a more progressive approach through the TPKS law and the Criminal Code, there is still a significant gap between legal norms and social practice. Therefore, synergy between the government, law enforcement officials, Indigenous leaders, and civil society is needed to strengthen legal protection and ensure the effective fulfillment of women’s rights.